TEKNOLOGI FERMENTASI PADA PEMBUATAN PAKAN TERNAK RUMINANSIA BERBAHAN BAKU ECENG GONDOK (Eichornia crassipes) - Herlina Fitrihidajati; Evie Ratnasari; Isnawati Isnawati; Gatot Soeparno (Universitas Sebelas Maret, 2014)
Water hyacinth (Eichhornia crassipes) is an aquatic weed that grows in the surface of water. It’s rapidly growth can disturb the aquatic ecosystem. The water hyacinth has a potential to become the food supplement of animal because of its high protein content, but the crude fiber content which is difficult to be digested by the animal. So that, it’s needed some treatment of water hyacinth to become an animal feeding which have a low crude fiber content using technology fermentation. The purpose of this research is to know the result of water hyacinth fermentation on the various concentration of bio-activator. The method that was used is by fermenting the water hyacinth in the various concentration of yeast include 0 g/Kg (V0), 14 g/Kg (V1), 17,5 g/Kg (V23), 21 g/Kg (V3) dan 24,5 g/kg (V4) for 5 days. The feeding of the fermentation result from the various treatment then was analyzed its protein level and crude fiber content, and also the physical structure. The Physicly of water hyacinth fermentation result was has a crumb structure, has a dark brown colour and has a smell like tempe. From the proximate analysed, was known that V1 treatment (14g/kg) contained of the best nutrition that had the highest rough protein content (11,09%) and the low crude fiber content (21,16%). Keywords: fermentation technology, animal feeding, ruminants and water hyacinth.